An injectable, self-healing, anti-infective, and anti-inflammatory novel glycyrrhizic acid hydrogel for promoting acute wound healing and regeneration - Guo, Qiyou; Li, Ruojing; Zhao, Yeying; Wang, Huibo; Luo, Wenqiang; Zhang, Junhao; Li, Zhenlu; Wang, Peige (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionBacterial infection, a complex wound microenvironment, and a persistent inflammatory response in acute wounds can result in delayed healing and abnormal scar formation, thereby compromising the normal function and aesthetic appearance of skin tissue. This issue represents one of the most challenging problems in clinical practice. This study aims to develop a hydrogel dressing specifically designed for the treatment of acute wounds, providing immediate and effective protection for the affected areas. This innovation seeks to offer a novel and advanced solution for the management of acute wounds.MethodsIn this study, a composite hydrogel scaffold was synthesized through the reaction between oxidized glycyrrhizic acid and carboxymethyl chitosan Schiff base. The material properties of the hydrogel were systematically characterized, and its biocompatibility and antibacterial efficacy were rigorously evaluated. A rat wound model was established to compare multiple groups, thereby assessing the impact of the hydrogel on the wound microenvironment and wound repair.ResultsThe results demonstrated that the OGA-CMCS hydrogel exhibited excellent injectability, biocompatibility, and antibacterial properties. It was capable of enhancing the wound microenvironment, which in turn influenced the polarization of macrophages from the M1 to the M2 phenotype, thereby mitigating the inflammatory response, promoting angiogenesis and granulation tissue regeneration, and accelerating wound healing.DiscussionThis study successfully developed a novel glycyrrhizin-based hydrogel dressing, which not only introduces innovative approaches for the emergency management of acute surface wound defects but also provides an experimental foundation. It is anticipated to contribute significantly to addressing relevant clinical challenges.